Perbandingan Sekuens Konsensus Gen Hemaglutinin Virus Avian Influenza Subtipe H5N1 Asal Unggas di Indonesia dengan Subtipe H5N2 dan H5N9 - I Gusti Ngurah Kade Mahardika; I Nyoman Suartha; Ida Bagus Kade Suardana; I Gusti Ayu Yuniati Kencana; I Wayan Teguh Wibawan (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2009)
Consensus sequence of hemagglutinin (HA) gene of avian influenza viruses of H5N1 subtype isolatedfrom fowl in Indonesia – hereafter named as H5N1_Indonesia – is compared with that of H5N2 and H5N9viruses. Sequence information were downloaded from the public database GeneBank. The genetic distancesand nucleotide as well as its deduced amino-acid sequence alignment were analysed. At nucleotide level,genetic distances of HA between H5N1_Indonesia to H5N2 and H5N9 are 16.2% and 9.6%, respectively.At amino-acid level, the distances are 9.7% and 6.8%. The genetic distances of HA1 fragments are 19.0%(H5N1_Indonesia – H5N2) and 10.9% (H5N1_Indonesia – H5N9). At amino-acid, level the genetic distancesof HA1 are 13.1% (H5N1_Indonesia-H5N2) and 8.8% (H5N1_Indonesia – H5N9). All three subtypes havedifferent glycosilation motive and variation of amino-acid sequence of four antigenic sites. The consequenceof those facts is discussed.